Inclusión educativa de estudiantes con Síndrome de Asperger en la Unidad Educativa Particular San Gerardo en la ciudad de Loja en el periodo 2023-2024. - Hurtado Flores, María Fernanda (2023)
The present thesis research entitled Educational Inclusion of students with Asperger Syndrome in the San Gerardo Private Educational Unit in the city of Loja in the period 2023-2024, is focused on the work done in the Institution together with the main actors of the present problem which are the students with Asperger Syndrome, mothers/parents and teachers tutors of the UEPSG. The main objective of the research work is to analyze the inclusive education of students with Asperger's syndrome of the particular educational institution San Gerardo of the city of Loja in the year 2023-2024. The purpose of the research is to describe the process of family support in educational inclusion, explain the methodological strategies used by teachers in the inclusion process, and identify factors that are beneficial for students with Asperger syndrome involving policies institutions, in the local and national environment. This research is methodologically developed under an inductive study method, with a qualitative, descriptive and phenomenological research approach, for the elaboration of the theoretical framework a bibliographic analysis was conducted, to obtain direct information an interview was conducted with mothers and fathers and teachers tutors of students in ninth and tenth year of EGB. With the research, a greater inclusion of students with Asperger's syndrome was achieved and teachers learned better methodological strategies to be implemented in the classroom with the implementation of visual resources, Tic's, given that the type of teaching of the teacher is deepened and adapted for students with special educational needs. The accompaniment of mothers/parents is crucial and fundamental for the teaching-learning process, where they will be immersed in the student's academic and recreational activities.